2021
DOI: 10.4018/978-1-7998-4489-1.ch002
|View full text |Cite
|
Sign up to set email alerts
|

International Student Mobility in ASEAN

Abstract: This chapter will examine the present context where international student mobility in the ASEAN region is concerned. It will look at how national policy, regional policy, and specific mobility initiatives are functioning to support the creation of an ‘ASEAN Student Mobility' regional hub. In particular, the chapter will explore how these efforts relate to existing theoretical models that that exist to explain student mobility and whether they are framed in terms of this theoretical thinking. The chapter will c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 15 publications
0
14
0
Order By: Relevance
“…Vietnam-bound ISM is, first, characterised by diplomatic and economic relations between Vietnam and the sending countries of international students. This trend is evident in the dominant majority of international students in Vietnam come from Cambodia and Laos, its two neighbouring countries (Atherton et al, 2020;MOET, 2022). Vietnam's more recent ties with South Korea have also given rise to the presence of Korean nationals in Vietnamese HEIs, especially in Vietnamese studies undergraduate programmes or short-term language and culture courses as shown in the works of Phan et al (2022) and Khanh and Ngoc (2023a, b).…”
Section: International Students In Vietnammentioning
confidence: 99%
See 2 more Smart Citations
“…Vietnam-bound ISM is, first, characterised by diplomatic and economic relations between Vietnam and the sending countries of international students. This trend is evident in the dominant majority of international students in Vietnam come from Cambodia and Laos, its two neighbouring countries (Atherton et al, 2020;MOET, 2022). Vietnam's more recent ties with South Korea have also given rise to the presence of Korean nationals in Vietnamese HEIs, especially in Vietnamese studies undergraduate programmes or short-term language and culture courses as shown in the works of Phan et al (2022) and Khanh and Ngoc (2023a, b).…”
Section: International Students In Vietnammentioning
confidence: 99%
“…In recent years, both Cambodia and Laos have witnessed steady and increasing outflows of students engaging in higher education abroad (Atherton et al, 2020). In terms of destinations, Vietnam is the top choice for Laotian students (Chao, 2020), and one of the most popular host countries for those from Cambodia (Phirom, 2022).…”
Section: Cambodian and Laotian Students In International Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…Malaysia was selected as the host country in this research because it is often regarded as an “education hub”, due in part to favorable government policies toward TNE as well as a large student market. Malaysia accounts for 40% of enrollments of ASEAN students that study abroad within the region ( Atherton et al, 2018 ), and TNE management processes in Malaysia are “generally well developed”, according to an analysis by the UK's Quality Assurance Agency for Higher Education ( QAA, 2020 ).…”
Section: The Malaysia Contextmentioning
confidence: 99%
“…During the COVID-19 crisis, student mobility and academic exchange were made available within the Asian region through innovative means and mixed modes of in-person and virtual channels. ASEAN representative bodies and member states provided more flexible ways of implementing “internationalism at home,” where less physical mobility and more virtual mobility are required to experience the curriculum’s internationalism (Atherton et al, 2021 ). Whether regionalization of higher education would shape the future of Chinese student mobility is open for further research.…”
Section: Reimaging International Learning In the Covid-19 Crisis Contextmentioning
confidence: 99%